2009
DOI: 10.1111/j.1743-6109.2009.01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function Improvement Following Surgery for Stress Incontinence: The Relevance of Coital Incontinence

Abstract: Introduction Little is known about the impact of surgery for stress urinary incontinence (SUI) on female sexual function, and results are conflicting. Aims We aimed to clarify the impact of surgery for SUI on female sexual function. Methods We analyzed data collected from two studies evaluating sexual function in women after placement of the tension-free vagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 40 publications
2
43
0
4
Order By: Relevance
“…Pace and Vicentini [22], in a similar study in 71 women showed 90.1% improvement in the FSFI scores at the postoperative 12 months in 71 women after TOT. Bekker et al [23] suggested that there was 21.3% improvement in sexual functions after urinary incontinence surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pace and Vicentini [22], in a similar study in 71 women showed 90.1% improvement in the FSFI scores at the postoperative 12 months in 71 women after TOT. Bekker et al [23] suggested that there was 21.3% improvement in sexual functions after urinary incontinence surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Coital incontinence is an important factor in determining sexual functions after anti-incontinence surgery [23]. The prevalence of coital incontinence ranges from 10 to 56% [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with others. 11,25,27,28 Twenty-two patients (10 in the SUI group and 12 in the POP group) who were sexually active preoperatively did not regain sexual intercourse, because they worried that sexual activity would affect the surgical outcome. This is considered to be another negative effect on FSF after anterior vaginal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Bekker et al (30) revisaron la cirugía para la IU en la función sexual de las mujeres sin encontrar cambios posquirúrgicos sobre la frecuencia o satisfacción en sus relaciones pero sí una disminución en la IU durante las mismas.…”
Section: Herramientas De Valoraciónunclassified
“…Varios clínicos investigadores han evaluado métodos de inyección de macroplástico que puede hacerse bajo anestesia local en un procedimiento ambulatorio para corregir la IU de estrés en mujeres y señalan que este implante es efectivo a corto, mediano y largo plazo, que es bien aceptado para corregir este síntoma y que tiene pocos efectos colaterales (30)(31)(32)(33). Tabla 2.…”
Section: Herramientas De Valoraciónunclassified